2021
DOI: 10.1098/rsos.201566
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for evaluating contact patterns and risk mitigation strategies for COVID-19 in English primary schools with application of structured expert judgement

Abstract: Personal contacts drive COVID-19 infections. After being closed (23 March 2020) UK primary schools partially re-opened on 1 June 2020 with social distancing and new risk mitigation strategies. We conducted a structured expert elicitation of teachers to quantify primary school contact patterns and how contact rates changed upon re-opening with risk mitigation measures in place. These rates, with uncertainties, were determined using a performance-based algorithm. We report mean number of contacts per day for fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…For June 2020, we were unable to obtain detailed national figures for Cohorts 3 and 4 because DfE attendance information was not broken down into primary and secondary schools (and may have included some private sector schools). Instead, we drew on information from an elicitation of teachers in 36 primary schools in the Royal Society Schools network, described in a companion study [1]; key aspects of that elicitation study are reported in electronic supplementary material, Appendix A1. These elicited judgements projected an average 65% return of teachers and 58% return of other staff for early June 2020, noting considerable variations between individual schools.…”
Section: Data Sources For Model Inputsmentioning
confidence: 99%
See 1 more Smart Citation
“…For June 2020, we were unable to obtain detailed national figures for Cohorts 3 and 4 because DfE attendance information was not broken down into primary and secondary schools (and may have included some private sector schools). Instead, we drew on information from an elicitation of teachers in 36 primary schools in the Royal Society Schools network, described in a companion study [1]; key aspects of that elicitation study are reported in electronic supplementary material, Appendix A1. These elicited judgements projected an average 65% return of teachers and 58% return of other staff for early June 2020, noting considerable variations between individual schools.…”
Section: Data Sources For Model Inputsmentioning
confidence: 99%
“…By contrast, asymptomatic carriers may not be recognized at all. The in-school risk mitigation measures to reduce contacts between people, ensure hygiene and isolate persons who display possible COVID-19 symptoms [1] indicate they were effective in reducing opportunities for infection spread in June-July 2020.…”
Section: School Size Effectmentioning
confidence: 99%
“…Additionally, behavioural mitigation measures were instituted in March 2020 to reduce contacts within schools. To model the number of contacts, we use the results of a Structured Expert Judgement (SEJ) elicitation study [1] conducted in spring/summer 2020 in the UK. SEJ uses the collective knowledge of experts (here school teachers) to estimate quantities of interest and their uncertainties, and can be performed rapidly during crises to provide essential information to models and policy makers [11].…”
Section: Classroom Transmission Networkmentioning
confidence: 99%
“…However, school managers are responsible for deciding whether to continue to 'bubble' classes to minimize interactions. Teachers and school leaders may also decide to continue to implement measures that reduce contacts within the classroom, so we adopt the two contact rates distributions from [1] that model contact rates for pre-Covid classrooms and reduced contact rates during the epidemic. Incidence rates are obtained from a national scale epidemiological model [15] with scenarios modelling a gradual or rapid return to pre-pandemic societal contact rates.…”
Section: Forecast Scenariosmentioning
confidence: 99%
See 1 more Smart Citation